Drivers of soil organic carbon stocks at village scale in a sub-humid region of Zimbabwe - Nyawasha, R.W.; Falconnier, G.N.; Todoroff, P.; Wadoux, A.M.; Chikowo, R.; Conquerean, A.; Leroux, L.; Jahel, C.; Corbeels, M.; Cardinael, R. (Elsevier, 2025)
Land use change caused by agriculture and inappropriate agricultural management cause soil organic carbon (SOC) loss. This study was conducted in a smallholder communal area of Zimbabwe with the following objectives: i) to quantify SOC stocks under contrasting land uses and soil types, and estimate landscape-level SOC stocks, ii) to assess the impact of historical agricultural management parctices on SOC in croplands (homefields vs outfields), and iii) to estimate temporal changes in SOC stocks due to land use change using field measurements and geospatial data (Africa Soil Information Service, AfSIS). SOC stocks were measured across three soil types and eight land uses (croplands, gardens, fallows, grasslands, vleis, shrublands, forests and tree plantations) at soil depths of 0–20 and 20–40 cm. Estimates from AfSIS were also used for comparison. SOC stocks were highest on black clay soils (66.9 ± 2.30 Mg C/ha), followed by red clay soils (36.1 ± 2.04 Mg C/ha) and sandy soils (25.5 ± 0.59 Mg C/ha). Among land uses, SOC stocks were highest in vleis (67.9 ± 3.55 Mg C/ha), followed by gardens (56.4 ± 2.34 Mg C/ha) and grasslands (53.1 ± 6.18 Mg C/ha). Croplands on sandy soils had the lowest stocks (22.7 ± 0.77 Mg C/ha). Distance from homestead had no significant effect on SOC stocks. SOC stocks estimated by AfSIS were systematically underestimated in vleis, grasslands and gardens, resulting in a 20 % underestimation of landscape SOC stocks. Landscape SOC stocks declined slightly (−0.2 %) from 2002 to 2023, though the change was not statistically significant. Our findings highlight that SOC stocks hotspots are concentrated in vleis, gardens and grasslands, mostly within communal grazing lands. Their conservation should therefore be a priority, emphasizing the need for collective management. On the other hand, restoration of degraded croplands could be enhanced by strenghtening linkages between cultivated fields and communal grazing lands through improved livestock management.